2011
DOI: 10.1149/1.3577597
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Temperature Driven Flow in a Polymer Electrolyte Fuel Cell Using High-Resolution Neutron Radiography

Abstract: A temperature gradient is known to exist within the fuel cell components during operation and for sometime after shutdown. In this study, a controlled temperature gradient across a single fuel cell was quantitatively investigated using high-resolution neutron imaging. The direction of liquid water transport under isothermal and non-isothermal conditions was observed in both hydrophilic and hydrophobic diffusion media (DM). The change in distribution of liquid saturation with time revealed two different mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 63 publications
(143 reference statements)
1
51
0
Order By: Relevance
“…Neutron radiography is highly sensitive to liquid water in PEM fuel cell studies due to the high attenuation caused by hydrogen-containing atoms. This technique has therefore been very useful in liquid water transport research [30][31][32][33][34][35][36][37]. Neutron-based PEM fuel cell studies are generally limited to spatial resolutions of 25 μm at temporal resolutions of 5.4 s [25].…”
Section: Visualizations Of Liquid Water Saturationmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutron radiography is highly sensitive to liquid water in PEM fuel cell studies due to the high attenuation caused by hydrogen-containing atoms. This technique has therefore been very useful in liquid water transport research [30][31][32][33][34][35][36][37]. Neutron-based PEM fuel cell studies are generally limited to spatial resolutions of 25 μm at temporal resolutions of 5.4 s [25].…”
Section: Visualizations Of Liquid Water Saturationmentioning
confidence: 99%
“…Neutron-based PEM fuel cell studies are generally limited to spatial resolutions of 25 μm at temporal resolutions of 5.4 s [25]. However, researchers have achieved spatial resolutions as small as 15.4 μm with a temporal resolution of 54 s [30] and 2.5 μm with a temporal resolution of 5 minutes using specialized detection systems [31].…”
Section: Visualizations Of Liquid Water Saturationmentioning
confidence: 99%
“…PCI flow has been studied in the literature either by experimental in situ measurements 17,18 or using 1D non-isothermal, two-phase models to simulate water evaporation/condensation quantitatively. 19 The temperature-gradientinduced water flux measurements conducted by Mench et al 17,18 through a non-operating and operating fuel cell show the importance of the PCI flow at various temperatures. Weber et al 19 coupled thermal and water management together with a non-isothermal 1D model to investigate the transport of water due to the temperature gradient.…”
mentioning
confidence: 99%
“…There are a variety of methods to visualize how the produced water is removed from the reaction area, including optical visualization with transparent cells, 11 scanning electron microscopy (SEM), 12 X-ray radiography, [13][14][15][16] and neutron radiography. 17 Sasabe et al visualized water accumulation and discharge in an operating cell by a soft X-ray radiographic technique, and suggested that the MPL prevents the accumulation of water in the substrate layer. 13 Deevanhxay et al observed water accumulation and transport in the cathode side MPL and GDL, and suggested that the water generated from the cell reactions was transported to the GDL mainly through cracks in the MPL.…”
mentioning
confidence: 99%